Slovak Republic : 2012 Article IV Consultation; Staff Report; Informational Annex; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2012)
Strong exports in the Slovak Republic supported a healthy economic expansion with real GDP growing 3.3 percent in 2011. The 2012 Article IV Consultation highlights that the robust performance of net exports offset the contraction in domestic demand amid fiscal consolidation and volatile consumer confidence. Executive Directors have commended the prudent macroeconomic policies and sound fundamentals that have underpinned a strong recovery for the Slovak economy. Directors have also supported the authorities' consolidation strategy to achieve fiscal sustainability.